The Role of Employee Benefits in Retaining Top Talent: A Case Study of Kawacom Uganda Limited Namanve - Joy Tatuleka (Uganda Christian University, 2024)
In today's competitive business landscape, retaining top talent is crucial for organizational success. Employee benefits play a significant role in attracting and retaining skilled employees. This study investigated the role of employee benefits in retaining top talent at Kawacom Uganda Limited. A mixed-methods approach was employed, combining both quantitative and qualitative data collection and analysis methods using a correlation design. A questionnaire survey was administered to 55 employees, and in-depth interviews were conducted with 10 HR managers and employees. The study found that both financial and non-financial benefits are essential in retaining top talent. Competitive salary, bonuses, and retirement plans were identified as key financial benefits, while flexible work arrangements, training and development, and employee recognition were identified as key non-financial benefits. The study's findings suggest that employee benefits are a critical factor in employee retention and that organizations should consider offering a range of benefits to attract and retain top talent. The study's results have implications for HR practices and policies in Kawacom Uganda Limited and other organizations seeking to retain top talent in a competitive labor market.